With a little help from my friends : cooperation and competition in mixed-species biofilms. - Goh, Joee Jie Xuan. (2013)
Extracellular polysaccharide is essential in biofilm establishment. Pseudomonas aeruginosa produces three types of polysaccharides, alginate, Pel and Psl. Non-mucoid strains, such as PAO1 used in the study, rely mainly on Psl polysaccharide as an attachment factor for biofilm development. Studies performed in mono-species biofilm revealed that the Pel gene disrupted mutant produce a biofilm structure identical to wild-type PAO1 biomass, while the Psl mutant had poor biofilm growth. Also, structural redundancy exists between Pel and Psl, allowing the Psl mutant to compensate for Pel polysaccharide production. In this study, I investigated the roles of Pel and Psl polysaccharide in biofilm development when competing with other bacteria in a mixed-species biofilms. PAO1∆pel and PAO1∆psl were tagged with yellow fluorescent protein, grown respectively with cyan fluorescent protein tagged Pseudomonas protegens Pf-5 and Ds-Red tagged Klebsiella pneumonia Kp-1 as a mixed-species biofilm. Results from continuous-culture flow cell indicated that the biofilm composition of PAO1∆pel and PAO1∆psl in mono-species can be extrapolated to the mixed-species system. Structural redundancy neither occurred nor assisted PAO1∆psl-eYFP to compete in mixed-species biofilm. PAO1∆pel-eYFP and PAO1∆psl-eYFP displayed reduced phenotypic variability when grown in mixed-species biofilm, suggests that their phenotypic variants have shared function with Pf-5-eCFP phenotypic variants.